2015
DOI: 10.1007/s00223-015-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone Characteristics and Their Determinants in Adolescents and Young Adults with Early-Onset Severe Obesity

Abstract: Childhood obesity is associated with compromised bone health. We studied bone characteristics and their determinants in obese young adults. The study included 68 subjects with early-onset severe obesity and 73 normal-weight controls. Data on physical activity (PA), diet and smoking were collected. Bone characteristics were measured using peripheral QCT. The obese and control subjects were similar in age (mean 19.6 ± 2.6 years) and height but BMIs differed (39.7 and 22.6 kg/m(2)). A clustering of unhealthy life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Written informed consent was obtained from all study participants and in case of minors, the consent was obtained from their legal guardians as well. Inclusion criteria for the obese subjects were: i) weight-for-height ratio exceeding 60% before age 7 years, according to Finnish growth standards (comparable to BMI > 97 th percentile for age), ii) referral because of severe obesity to Children's Hospital, Helsinki University Hospital, during childhood, iii) residence in the capital region of Helsinki at age 7 years, and iv) aged between 15 and 25 years at the time of the study, as described earlier [10]. We identified a total of 366 patients fulfilling the inclusion criteria in the hospital's patient register and 68 (19%) of them consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Written informed consent was obtained from all study participants and in case of minors, the consent was obtained from their legal guardians as well. Inclusion criteria for the obese subjects were: i) weight-for-height ratio exceeding 60% before age 7 years, according to Finnish growth standards (comparable to BMI > 97 th percentile for age), ii) referral because of severe obesity to Children's Hospital, Helsinki University Hospital, during childhood, iii) residence in the capital region of Helsinki at age 7 years, and iv) aged between 15 and 25 years at the time of the study, as described earlier [10]. We identified a total of 366 patients fulfilling the inclusion criteria in the hospital's patient register and 68 (19%) of them consented to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometry including height (cm), weight (kg), and waist (WC; cm) and hip circumferences (cm) was collected during the study visit and BMI (kg/m 2 ) calculated, as described previously [10]. The health and diseases of the subjects, and their use of medicines were self-reported and collected with a questionnaire [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI was calculated as weight divided by square height (kg/m 2 ). Lifestyle factors including smoking, alcohol use and current total physical activity, and use of medications were evaluated with questionnaires as described previously [22]. Less than 10 min of total physical activity per day was considered a threshold for a sedentary lifestyle.…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that in subjects with severe childhood-onset obesity bone strength is more likely to be compromised in men than in women [22]. This prompted us to evaluate testicular function and related skeletal features in males with severe childhood-onset obesity.…”
Section: Introductionmentioning
confidence: 99%